Extracellular matrix stiffness activates mechanosensitive signals but limits breast cancer cell spheroid proliferation and invasion - Jahin, Irina; Phillips, Thomas; Marcotti, Stefania; Gorey, Mark-Alexander; Cox, Susan; Parsons, Maddy (Frontiers in Cell and Developmental Biology, 2023)
Breast cancer is characterized by physical changes that occur in the tumor microenvironment throughout growth and metastasis of tumors. Extracellular matrix stiffness increases as tumors develop and spread, with stiffer environments thought to correlate with poorer disease prognosis. Changes in extracellular stiffness and other physical characteristics are sensed by integrins which integrate these extracellular cues to intracellular signaling, resulting in modulation of proliferation and invasion. However, the co-ordination of mechanosensitive signaling with functional changes to groups of tumor cells within 3-dimensional environments remains poorly understood. Here we provide evidence that increasing the stiffness of collagen scaffolds results in increased activation of ERK1/2 and YAP in human breast cancer cell spheroids. We also show that ERK1/2 acts upstream of YAP activation in this context. We further demonstrate that YAP, matrix metalloproteinases and actomyosin contractility are required for collagen remodeling, proliferation and invasion in lower stiffness scaffolds. However, the increased activation of these proteins in higher stiffness 3-dimensional collagen gels is correlated with reduced proliferation and reduced invasion of cancer cell spheroids. Our data collectively provide evidence that higher stiffness 3-dimensional environments induce mechano-signaling but contrary to evidence from 2-dimensional studies, this is not sufficient to promote pro-tumorigenic effects in breast cancer cell spheroids.pave the way for studying longer-term impacts of stiffness-induced transcriptional changes that may mediate tumor progression and drug response in cancer.Primary antibodies used were ERK1/2 and ppERK1/2 (Cell Signaling Technology; #9102 and #9101 respectively), GAPDH (GeneTex; GTX627408 ), anti-species Horseradish Peroxidase (HRP) -conjugated secondary antibodies (Dako), AlexaFluor-conjugated secondary antibodies (Thermo Fisher Scientific),